The lingering conflict : Israel, the Arabs, and the Middle East, 1948-2012 - Rabinovich, Itamar, 1942- (Brookings Institution Press, 2013)
"A detailed history and analysis of Arab-Israeli relations and the conflict between two peoples claiming the same land, exploring through firsthand experience how these relations have been shaped over the years and assessing the prospects for a peaceful future"--Provided by publisher.